Amended description of Aspidistra foliosa (Asparagaceae, Convallarioideae), and a new combination, Aspidistra foliosa var. zinaidae - Tillich, Hans-Juergen (Phytotaxa, 2025)
An amended description of the hitherto incompletely described Aspidistra foliosa is given, including the description of a new combination, A. foliosa var. zinaidae.